THE INFLUENCE OF ROLE-PLAYING METHOD ON THE SOLUTION OF MATHEMATICAL STORY PROBLEMS IN ELEMENTARY SCHOOLS - Neneng Zakia; Yayan Alpian; Anggy Giri Prawiyogi (Universitas Majalengka, 2024)
Mathematics plays a crucial role in shaping students' thinking patterns to face daily life challenges. However, many students struggle with solving mathematical story problems, making the low ability of students in solving mathematical story problems a serious concern. This study aims to examine the effect of the role-playing method on students' ability to solve mathematical story problems in the topic of numbers in fifth-grade students at SDN Palumbonsari 1. This research uses a quantitative descriptive experimental approach with a Pretest Post-test Nonquivalent Control Group design. The sample of this study is fifth-grade students at SDN Palumbonsari 1 selected randomly, with class VC as the experimental group (role-playing method) and class VB as the control group (conventional method). The instrument used is an essay test that has been validated and tested on students outside the research sample. Data analysis was performed using normality and homogeneity tests, as well as hypothesis testing with Paired Samples Test. The results of data analysis show that there is a significant difference between the average learning outcomes of students before and after the treatment. Students who received learning with the role-playing method showed a more significant improvement in their ability to solve mathematical story problems compared to students who received conventional learning. In conclusion, the use of the role-playing method in mathematics learning can improve students' ability to solve mathematical story problems. This method makes learning more meaningful, enjoyable, and can increase student engagement in learning.